Merdeka Curriculum implementation at Granada Islamic Integrated and Dhuhaa Islamic Junior High School in Tangerang City - Dinda Adiesty Kusumawardani; Lenny Sapitri; Mia Roosmalisa Dewi (Universitas Pendidikan Indonesia, 2022)
The main support for achieving the goals of quality Indonesian human development is education. The implementation of quality education always demands transformation in every process and stage, this is because there are always dynamic constraints and problems that arise due to various situations and conditions. As a form of innovation in improving the quality of Indonesian education, Kurikulum Merdeka is implemented which has characters and characteristics that are believed to be able to answer the challenges of education in the 21st century in creating a quality generation of Indonesians. The research in this article is aimed at finding out the application of the Independent Curriculum in the learning process. in schools at the junior high school education unit level which is the Sekolah Penggerak. The research was conducted using a case study method with a convergent mixed methods approach. The results of the study show that the teachers at the Sekolah Penggerak have made optimal efforts in developing the learning process in accordance with the various core elements of the Kurikulum Merdeka.